Colonization by S. Aureusincreases the EASI and the number of appointments by patients with atopic dermatitis: cohort with 93 patients - Lipnharski,Caroline (2013)
BACKGROUND:Atopic dermatitis leads to epidermal barrier dysfunction and bacteria colonization. The relationship of the last factor with the severity of the disease and the frequency of exacerbation is not fully known.OBJECTIVES:Verify the severity of the atopic dermatitis and the number of appointments generated by dermatosis, comparing patients colonized with patients not colonized by S. aureus. Verify the frequency of colonization by methicillin resistant Staphylococcus aureus acquired in the community.METHODS:Cohort study with a 12 months follow-up, in a sample of patients from Porto Alegre, RS public network. Cultures in active injuries and nasal cavities were carried out as well as methicillin sensitivity tests to S. aureus.The severity of atopic dermatitis was defined by Eczema Area and Severity Index (EASI).RESULTS:We included 93 patients, 43% female and 56% male, 26 colonized by S. aureusin the nasal orifices, 56 in the skin damage. The mean of initial Eczema Area and Severity Index was 5.5 and final 3.9. The initial Eczema Area and Severity Index of patients colonized by S. aureusin the skin and nasal cavity was larger than the number of patients without colonization(p< 0.05). During the period of one year, in average, there were six appointments/patient. There was linear correlation between the number of appointments during one year and the inicial Eczema Area and Severity Index (r = 0,78). There were no patients with methicillin resistant Staphylococcus aureus acquired in the community.CONCLUSION:There is a relevant influence of staphylococcal colonization on the severity of atopic dermatitis and the number of appointments required by its exacerbation. Methicillin resistance among those affected by S. aureusdoes not seem to be an emergent problem, in this Brazilian sample.